Comparative Analysis of Essential Oil Profiles From Emprit Ginger Rhizome (Zingiber officinale var. amarum) Grown in Different Locations and Antibacterial Activity Againts Staphylococcus aureus - Styawan, Anita Agustina; Purwanto; Susidarti, Ratna Asmah; Windarsih, Anjar; Rohman, Abdul (Indonesian Journal of Tropical and Infectious Disease, 2024)
Indonesia, as a tropical country, boasts significant biodiversity, particularly regarding its flora and fauna. The country's medicinal plants are one inherited natural resource passed down through generations. The "emprit ginger” (Zingiber officinale var. amarum), a native Indonesian medicinal plant, is often employed in treating various diseases. Scientifically, the primary constituent of emprit ginger is the phenolic ketone homolog compound, gingerol, known for its antioxidant activity. In addition to its antioxidant potential, emprit ginger exhibits potential as an antibacterial agent. However, herbal substances used for therapeutic purposes often yield inconsistent effects due to the fluctuating chemical composition in the plants, typically a result of varying growing locations. These location differences can cause discrepancies in the content of active metabolites. Therefore, data on the chemical profile of medicinal plants is paramount for the standardization process. This study was conducted by obtaining essential oils from the rhizomes of emprit ginger, extracted via steam distillation obtained from various cultivation lands in Ponorogo, Magetan, Pacitan, Wonogiri, Karanganyar, Boyolali, Semarang, Magelang, Purworejo, Temanggung, Wonosobo, Banyumas, Bantul, and Kulonprogo. One of the efforts in standardizing natural materials involves the analysis of their metabolite profiles. The emprit ginger essential oil profile was obtained through Gas Chromatography-Mass Spectrometry (GCMS) testing. The emprit ginger essential oil profile was analyzed using a multivariate calibration of Principal Component Analysis utilizing SIMCA 17 software. Antibacterial activities were assessed using the microdilution method on Staphylococcus aureus bacteria. The analysis of antibacterial activity was determined using the Probit analysis method to ascertain the Minimum Inhibitory Concentration (MIC) 50 value. This study also involved the extraction of essential oils from emprit ginger rhizomes. The individual profiles of these essential oils were determined via Gas Chromatography Mass Spectrometry. The essential oil profiles of emprit ginger were subjected to a multivariate calibration using Principal Component Analysis facilitated by the SIMCA 17 software. Antibacterial activity tests were conducted using the microdilution method on Staphylococcus aureus bacteria. The antibacterial activity was ascertained using probit analysis to derive the Minimum Inhibitory Concentration 50 (MIC 50) values. The highest MIC 50 of emprit ginger rhizome on Staphylococcus aureus bacteria was found in samples from Wonogiri, with a concentration of 0.3408%. Compounds displaying significant discriminative influence on Staphylococcus aureus bacteria included Z-Citral, Geranyl acetate, Zingiberenol, Beta-Myrcene, (1S0-2,6,6-Trimethylbicyclo [3.1.1] hept-2-ene, and Bicyclo [2.2.1]heptan-2-ol, 1,7,7-trimethyl, exo-(CAS)